Total remission of Merkel cell carcinoma after coronavirus infection: a case report - Lucas Henrique Rigon Vidoto; Cicero Luiz Cunha Martins; Andreia Cristina De Melo (Brazilian Journal of Oncology)
A 65-years old Peruvian woman was admitted to the Brazilian National Cancer Institute, with a diagnosis of Merkel cell carcinoma in the left shoulder. A PET-CT confirmed the locally advanced disease, with the involvement of lymph nodes in the axillary region. At the time of the proposed surgical procedure, the patient tested positive for COVID-19 without symptoms. She returned for an appointment one month later recovering from COVID-19, reporting a significant decrease in the lesion. One month later, no lesion was clinically found on the left shoulder. Due to the possible remission of the disease, a new PET CT was requested, revealing no metabolic findings suggestive of active neoplastic tissue.